Analisis Dampak Kebijakan Moneter terhadap Pertumbuhan Ekonomi di Indonesia - Hari Winarto; Adi Poernomo; Agus Prabawa (Universitas Batanghari, 2021)
The circuit of government monetary policy which is still uncertain in influencing economic growth is an interesting phenomenon to be examined, especially because it occurs in the era of globalization where monetary traffic is very rapid, the situation is the main problem in this study. Therefore, this study aims to determine the impact of monetary policy on economic growth in Indonesia using quantitative analysis methods. The type of data used is secondary data in the form of Time Series originating from the Central Statistics Agency, Bank Indonesia, and the Ministry of Trade from 2010 to 2019 in the form of quarterly. Based on the results of testing the determination of the analysis tool model shows that the right estimation model is Vector Auto Regression (VAR). The results of this study indicate that money supply has a significant relationship to economic growth. While interest rates, exchange rates, and inflation do not have a significant relationship to economic growth